MEMBANGUN GOOD GOVERNANCE DALAM MEWUJUDKAN ORGANISASI PELAYANAN PUBLIK BERBASIS KINERJA - Luh Kartika Ningsih (ARTHA SATYA DHARMA, 2017)
The purpose of this study was to determine how to establish good governance inthe realization of performance-based public services in Buleleng regencygovernment. This study uses a quantitative approach. Data collection techniquesused in this study was a questionnaire / questionnaire measuring devices in theform of Agree-Disagree Scale, which were selected for the study is the structuralofficials from several agencies selected in the Regency. Buleleng as many as 108people. Data analysis techniques used in this study is a structural equation model(Structural Equation Modeling-SEM) based variance or Component based SEM,the famous so-called Partial Least Square (PLS) Visual version 2.0. Allrelationships are examined in this study showed significant results related to thepresence of good governance in realizing the performance of public serviceorganizations. To that end in the realization, Buleleng regency government isexpected to improve organizational performance by creating good governance.realization of organizational performance, it is the impact of the presence ofServant Leadership, Organizational Citizenship Behavior, and Godd Governancewhich will have an impact on improving government services to the public inBuleleng regency